2012
DOI: 10.1097/cji.0b013e318247a5e9
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Host Natural Killer Cell Functions in Breast Cancer via Prostaglandin E2 Receptors EP2 and EP4

Abstract: Breast malignancies often have high levels of COX-2. The COX-2 product prostaglandin E2 (PGE2) contributes to the high metastatic capacity of breast tumors. Our published data indicates that inhibiting either PGE2 production or PGE2-mediated signaling through the PGE2 receptor EP4 (one of four EP expressed on the malignant cell) reduces metastasis by a mechanism that requires Natural Killer (NK) cells. Tumor derived PGE2 and exogenous PGE2 are known to have direct inhibitory effects on NK cell functions, but l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 16 publications
0
62
0
Order By: Relevance
“…Considerable research has reported that NK cells express all PGE2 EP receptors and that PGE2 acts on NK cells through the EP2 and/or EP4 receptor subtypes, [73][74][75] which are known to be powerful activators of the adenylate cyclase system. 70 Since the adenylate cyclase system is involved in inhibiting killing by NK cells and inducing the CD94/NKG2A inhibitory NK receptor following PGE2 signaling, 76 it is not surprising that PGE2 has an inhibitory effect on NK cell function.…”
Section: 68mentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable research has reported that NK cells express all PGE2 EP receptors and that PGE2 acts on NK cells through the EP2 and/or EP4 receptor subtypes, [73][74][75] which are known to be powerful activators of the adenylate cyclase system. 70 Since the adenylate cyclase system is involved in inhibiting killing by NK cells and inducing the CD94/NKG2A inhibitory NK receptor following PGE2 signaling, 76 it is not surprising that PGE2 has an inhibitory effect on NK cell function.…”
Section: 68mentioning
confidence: 99%
“…40 Given the synthesis of large amounts of PGE2 by such activated professional APCs and because NK cells expressed all known EP receptors, 73 it is not surprising that DCs can modulate NK cell activity through the paracrine effects of the endogenously released PGE2 during DC-NK cell crosstalk. In fact, DC-mediated NK-cell effector functions are influenced by PGE2.…”
Section: Effects Of Pge2 On Dc-nk Cell Crosstalkmentioning
confidence: 99%
“…Recent research [69] has reported that NK cells express all PGE2 EP receptors and that PGE2 acts on NK cells through the EP2 and/or EP4 receptor subtypes, which are known to be powerful activetors of the adenylate cyclase system. The adenylate cyclase system is involved in inhibiting killing by NK cells and inducing the CD94/NKG2A inhibitory NK receptor following PGE2 signaling [70], and for this PGE2 has an inhibitory effect on NK cell function.…”
Section: Prostaglandinsmentioning
confidence: 99%
“…S6). Because several studies have shown that PGs contribute to the suppression of NK cell function 19,27 , we determined the levels of serum PGs using LC-MS/MS. Compared with the control group, the CRS group had significantly higher levels of PGD 2 but not PGE 2 (Fig.…”
Section: Nk Cells Regulate Eosinophilic Inflammation In a Murine Modementioning
confidence: 99%